Comparison of the Mechanical Energy Transfer of Gait in Female Athletes with and without Non-Specific Chronic Low Back Pain - Rahman Sheikhhoseini; Mohadese Kavianifard; Seid Esmail Hoseini Nejad; Hashem Piri (Women’s Health Bulletin, 2020)
Background: Low back pain (LBP) is one of the prevalent injuries among athletes. This study aimed to compare the mechanical energy transfer of gait in female athletes with and without non-specific chronic low back pain. Methods: In this cross-sectional study, based on convenience sampling method, we selected a total of 14 females with NSCLBP and 14 females without a history of LBP who referred to Tehran physiotherapy clinics . To capture marker trajectories and ground reaction forces, we used a Vicon 6 camera motion capture system (Vicon MX, Oxford Metrics, UK), which was synchronized with two ground embedded force plates (Kistler, Winterthur, Switzerland). We performed gait analysis in the biomechanics laboratory of the University of Social Welfare and Rehabilitation Sciences. The independent t-test analyzed the data. All analyses were performed at a confidence level of 95% (P<0.05). Results: The mechanical energy transfer in female athletes with LBP differed from athletes without LBP (P=0.037). There were no significant statistical differences between the ankle and knee joints regarding mechanical energy transfer (P>0.05). Conclusion: Our study showed that female athletes with LBP had higher eccentric mechanical energy compensation coefficient in the hip joint, which is possibly a compensatory mechanism for lumbosacral region disorders.